La acción mediadora de la danza urbana Break Dance frente al conflicto escolar (2019)
This research proposes to analyze the urban dance break dance in the mediation processes of the school conflict of the students of the 6 ° C course of the Educational Institution. For this purpose, objectives oriented to characterize in the first place the current state of the school conflict in the students, show and establish the mediating function that is given through the urban dance Break Dance. The methodology used was under the quantitative qualitative approach, through experimental research, transversal type. The population under study was comprised of 120 6th grade students, aged between 12 and 17, both female and male, enrolled in the Industrial Technical Educational Institution San Antonio de Padua headquarters 2, located in the Municipality of Soledad, the selected sample was 40 students of 6 ° C grade, representing 30% of the population object of this study, which was chosen by the simple random method, for the collection of information the participants were observed, direct observation, which allowed to determine the tastes of the student population by the urban culture break dance and the application of a contentive questionnaire of 16 questions, which 16 with fan-type answers from which results will be obtained, which were statistically evaluated and analyzed , where it was concluded that the school conflict is evident and the need to think of a tool as a mediator a of the conflict, for this the dance is taken not only as an artistic manifestation but as a socializing element; being the break dance (dance expression of Hip Hop) the genre that attracts these young people with difficulties in their family nucleus, in search of identity, of friends, of a social group that brings it together, accepts it and provides a “solution” to their problems, they find in the group a place to give their opinions, dialogue and something like mutual protection.